IJPE 2018
DOI: 10.23940/ijpe.18.03.p1.397412
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional Method of Fault Determination with Data-Driven Approach for Ball Bearings in a Wind Turbine Gearbox

Abstract: Android OS maintains its dominance in smart terminal markets, which brings growing threats of malicious applications (apps). The research on Android malware detection has attracted attention from both academia and industry. How to improve the malware detection performance, what classifiers should be selected, and what features should be employed are all critical issues that need to be solved. Convolutional Neural Networks (CNN) is a typical deep learning technique that has achieved great performance in image a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Previous studies have identified the appropriate base wavelet function by examining the energy distribution of the 1-D signal at various bands of frequency ( Balavignesh, Gundepudi, Sabareesh, & Vamsi, 2018 ). However, the same criteria may not perform while analyzing the 2-D image.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have identified the appropriate base wavelet function by examining the energy distribution of the 1-D signal at various bands of frequency ( Balavignesh, Gundepudi, Sabareesh, & Vamsi, 2018 ). However, the same criteria may not perform while analyzing the 2-D image.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to its better generalization property and the ability to deal with multi-labeled data, SVM found many applications in the field of fault detection and health state identification of various industrial machinery. 18,41,42 The above-prepared feature vector datasets (I, II, and III) are channeled as input to SVM for discriminating the various health states of the multi-stage gearbox. The classification accuracies are displayed in Figure 12.…”
Section: Support Vector Machinementioning
confidence: 99%
“…Kankar et al., 2011a) reported that, SVM has registered the highest classification accuracies while classifying the bearing fault conditions compared to ANN. PCA is being used not only to classify the data but also to reduce the dimensionality of the data with minimal loss of the original data (Nembhard et al., 2014; Balavignesh et al., 2018). PCA is an orthogonal linear transformation such that the original data are transformed into a new spatial coordinate system.…”
Section: Introductionmentioning
confidence: 99%